KELAYAKAN FINANSIAL USAHA PETERNAKAN KAMBING PERAH PASCA ERUPSI MERAPI DI KECAMATAN PAKEM, KABUPATEN SLEMAN - , HAPSARI ANGGRAINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research was to determine the financial feasibility of the dairy goat farming after the eruption of Merapi in Pakem, Sleman. The research was conducted from July to December 2013. Respondents were the farmers from Ngudi Makmur Farmer Group and Etawa Lestari Farmer Group, and both of them were located in Pakem, Sleman. Respondents were chosen as purpossive sampling method with some criteria and each farmer group consists of 23 and 10 farmers. The data were collected with survey method and questionnaire. The data were tabulated and made into cash flow with 5 years period, then analyzed with financial and sensitivity analysis. The criterias of financial feasibility were B/C, NPV, and IRR with 12% df per annum. The result showed that the dairy goat farming of the farmer's existing condition was feasible with NPV